Peningkatan Literasi Bahasa Inggris pada Siswa Sekolah Dasar melalui English Camp di Desa Mblengor Kulon - Asroriyah, Atik Muhimatun; Nabila, Zulfa; Mitsalina, Endah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This study aims to examine the effectiveness of the English Camp method in improving the English language skills of elementary school students in Mblengorkulon Village. The training was carried out by involving students from various grade levels. This training method involves a practical and interactive approach with a focus on vocabulary recognition, basic grammar and English speaking skills. The English Camp is held for 1 week in a row, with various activities such as games, speaking practice, and simulations of communication situations in English. The results of this study indicate a significant increase in the English literacy of elementary school students after attending the English Camp. This improvement is reflected in an increase in vocabulary comprehension, speaking ability, and confidence in using English in real situations. In addition, participation in the English Camp also provides valuable experience in broadening students' cultural insights. Community involvement in the implementation of the English Camp also helps strengthen students' understanding of the importance and benefits of English literacy. Collaboration between schools, teachers and the community is the key to success in implementing this program. Based on these findings, it is suggested that English training through the English Camp method can be adopted as a strategy to increase English literacy in elementary schools. Furthermore, this program can be expanded to other villages by involving the local community and society in order to provide wider access for students to develop their English skills